THE COMPARISON STUDY ON TWO-TYPES OF STUDENTS` PERSONALITY: SANGUINE AND PHLEGMATIC TOWARD THEIR ENGLISH SPEAKING ABILITY - Lisa Rakhmanina; Feny Martina; Nevan Jayadi (PROJECT (Professional Journal of English Education), 2020)
The study is an attempt to find out the difference between Sanguine and Phlegmatic personality toward their speaking ability. The design in this study was comparative analysis design. The samples of this study were 44 students from Faculty of Law. Personality test was carried out to decide whether the students were categorized to the group of Sanguine or Phlegmatic. Furthermore, the researcher used personal description for monologue speaking technique for testing the students speaking skills. The data were analyzed by using t-test formula to investigate whether there was significant difference result between the Sanguine and the Phlegmatic students in their speaking skill. From the result of the study, it could be concluded that there was no significant different result between the Sanguine and the Phlegmatic students toward their speaking skill. It means, there were not any better students in speaking between both Sanguine and Phlegmatic students. Those two personalities, the Sanguine and the Phlegmatic students could perform better English speaking skill through their own personal way.Keywords:  Comparison Study, Sanguine, Phlegmatic, Speaking Ability